THE USE OF RAHN CONTRACTS IN SHARIA PAWNSHOPS AS A CAPITAL STRATEGY FOR PAMEKASAN FARMERS - Syifatullaili Syifatullaili; Maksum Maksum (STAI Asy-Syukriyyah, 2026)
This study aims to analyze the implementation of the rahn contract in Sharia Pawnshops to improve the economy of farmers in Kadur District, Pamekasan Regency. This research uses a qualitative approach with a case study type, with the research subjects including Sharia Pawnshop employees and farmers using rahn-based financing. Data was collected through interview, observation, and documentation techniques, then analyzed using the Miles and Huberman model interactively. The results of the study show that the rahn contract is effective in providing quick and easy access to capital for farmers, supporting the smooth running of agricultural production activities, and contributing to increasing household economic stability. However, its implementation still faces obstacles in the form of low financial literacy, dependence on collateral assets, and limited access to services in rural areas.